PENGARUH TECHNOLOGY ACCEPTANCE MODEL DAN PENGEMBANGANNYA DALAM PERILAKU MENGGUNAKAN CORE BANKING SYSTEM - Dessanti Putri Sekti Ari (University of Merdeka Malang, 2013)
The purpose of this study was to examine the antecedents that affected the acceptance of individuals in using theCore Banking System through the constructs Technology Acceptance Model and its development. Constructsused in this study were perceived usefulness, perceived ease of use, attitude, social influences, behavioral inten-tion, facilitating conditions, and behavior. Data were collected through survey methods. The samples of thisstudy were employees working in commercial banks in Malang Raya. This study used 136 respondents and wasanalyzed by smart PLS. The result of this study was that the construct of perceived usefulness and perceived easeof use in the Technology Acceptance Model affected attitude and behavior. Attitude and behavior in the Technol-ogy Acceptance Model and social influence which was the development of the Technology Acceptance Modelaffected behavioral intention to use the Core Banking System, as well as the construct of behavioral intention inTechnology Acceptance Model affected behavior, whereas construct of facilitating conditions which was thedevelopment of the Technology Acceptance Model did not affect the behavior on using the Core Banking System.